Auditory development and its significance: an awareness study among expectant mothers in Kottarakkara taluk, Kerala - Jacob, Geena; Srividya, A.; Babu, Praveena (International Journal Of Community Medicine And Public Health, 2024)
Background: Studying pregnant women’s awareness of auditory development’s importance, especially in India, is an underexplored area. Given mothers’ pivotal role in monitoring child development, their understanding of auditory development is crucial. Addressing this gap could reveal insights into early hearing issue detection. Method: The study utilized a questionnaire survey employing Cluster sampling, gathering data from 103 expectant mothers aged 18 to 35. Of these, 55 were experiencing their first pregnancy, while 48 were on their second. The 16 question survey explored hearing loss, early identification, auditory behaviour, and high-risk indicators. Results: The study found that pregnant women, on average, exhibited a 42.35% knowledge level regarding the importance of auditory development during gestation. However, their attitude towards this aspect was notably high at 81.53%. This suggests a lack of awareness about auditory development, despite a generally positive attitude among expectant mothers. Importantly, there was a statistically significant difference in knowledge between first-time and experienced mothers (p<0.05), with the latter group demonstrating higher awareness, likely due to having older children. Conversely, no significant difference was observed in attitude between the two groups (p>0.05). Conclusions: The study’s findings shed light on a crucial aspect: the significance of maternal knowledge concerning hearing and its development. This understanding is pivotal for successful early identification and intervention programs. The study’s contribution lies in revealing mothers’ perspectives and attitudes towards monitoring their child’s speech, language, and motor development, emphasizing the importance of this awareness for early intervention strategies.